Urgensi Perlindungan Hukum Terhadap Korban Pelecehan Seksual Secara Verbal - M. Taufik Hidayatulloh (Sanskara Hukum dan HAM, 2022)
The act of sexual violence is very concerning, considering its impact on the victim has serious consequences, such as humiliation, humiliation, humiliation, intimidation, and can even create stress and trauma. In addition, often and many victims do not have the courage to report for several reasons, such as verbal harassment which is still considered normal in Indonesia.. This research was conducted to find out the need to create a special legal basis regarding cases of verbal harassment and also to find out the need for the role of education in minimizing these crimes. This research can be seen through filling out a survey conducted for 3 days from February 6-9 2021 and filled in by 102 respondents then presented in the form of a pie chart. Based on the results of the study, it is necessary to make a legal basis regarding the case and also the role of educational institutions in efforts to minimize the case.